The effects of solid lubricants for space vehicle under the 10(-7) torr ultra-high vacuum - Kwak, Wonil; Lee, Yongbok; Lee, Woosub; Lee, Jeonkook (PROCEEDINGS OF ASIA INTERNATIONAL CONFERENCE ON TRIBOLOGY 2018 (ASIATRIB 2018), 2018)
In a space environment vehicle components as bearings, seals and gears use solid lubrication to have high wear resistance on their mission duration. Because conventional lubrication has not good performances in wide temperature range and can be evaporation at the rarely ambient condition like lunar surface. This work provides tribological discussion about the component and requirement of space tribology. Also Pin-on-disk test is described to determine the effect on the solid lubrication under the high vacuum condition (about 10(-7) ton). This paper will discuss the following: space mechanism components, solid lubrication, and factors affecting wear phenomenon under the high vacuum.